Unveiling the Identity of Wenwan Walnuts and Phylogenetic Relationships of Asian Juglans Species Using Restriction Site-Associated DNA-Sequencing - Mu, Xian-Yun; Sun, Miao; Yang, Pei-Fang; Lin, Qin-Wen (Frontiers in Plant Science, 2017)
Juglans species have considerable ecological and economic value worldwide. In China, Wenwan walnuts have been collected by aristocrats and noblemen for more than 2000 years. As a diversity center of Asian Juglans, five species are widely distributed in China. The most famous of these is Mahetao (J. hopeiensis), which is an uncharacterized species that is mostly cultivated. Wild J. hopeiensis individuals are very rare and are endemic to Hebei province. Because of the minimal variations in previously used molecular markers and the heterogeneity between chloroplast and nuclear genomes, determining the phylogenetic relationships among the Juglans species has been challenging, and has hindered subsequent evolutionary inferences. In this study, we collected enough materials for both cultivated and wild Mahetao to construct well-resolved phylogenetic trees for Asian Juglans species. We used a high-throughput genome-wide restriction site-associated DNA sequencing method. Consequently, the identity of J. hopeiensis has been clearly resolved. Our results indicate that J. hopeiensis is a hybrid of J. regia and J. mandshurica. However, J. hopeiensis, J. regia and J. sigillata should be considered as a single species from section Juglans. Additionally, J. ailantifolia, J. cathayensis, and J. mandshurica likely represent one species from section Cardiocaryon according to morphological and molecular studies. These results are supported by population structure analysis and morphological comparison. We propose that J. hopeiensis trees growing in the wild should be conserved because of the economic value of their nuts. These trees may be of particular importance to impoverished communities. Furthermore, they may serve as a valuable genetic resource relevant for enhancing the production of edible walnuts. The 2b-RAD method is a viable option for future phylogenetic studies of Juglans species as well as other plant species.